Time-resolved spectroscopy uncovers deprotonation-induced reconstruction in oxygen-evolution NiFe-based (oxy)hydroxides - Dan Wu; Longfei Hu; Xiaokang Liu; Tong Liu; Xiangyu Zhu; Qiquan Luo; Huijuan Zhang; Linlin Cao; Jinlong Yang; Zheng Jiang; Tao Yao (Nature Communications)
Abstract Transition-metal layered double hydroxides are widely utilized as electrocatalysts for the oxygen evolution reaction (OER), undergoing dynamic transformation into active oxyhydroxides during electrochemical operation. Nonetheless, our understanding of the non-equilibrium structural changes that occur during this process remains limited. In this study, utilizing in situ energy-dispersive X-ray absorption spectroscopy and machine learning analysis, we reveal the occurrence of deprotonation and elucidate the role of incorporated iron in facilitating the transition from nickel-iron layered double hydroxide (NiFe LDH) into its active oxyhydroxide. Our findings demonstrate that iron substitution promotes deprotonation process within NiFe LDH, resulting in the preferential removal of protons from the specific bridged hydroxyl group (Ni2+-OH-Fe3+) linked to edge-sharing [NiO6] and [FeO6] octahedron. This deprotonation behavior drives the formation of high-valence Ni3+δ species (0 <δ < 1), which subsequently serve as the active sites, thereby ensuring efficient oxygen evolution activity. This approach offers high-resolution insights of dynamic structural evolution, overcoming the limitations of extended acquisition times and advancing our understanding of OER mechanisms.